Analisis Kekuatan Mekanik Pipa Air dari Bahan Komposit Serbuk Kulit Kerang - Zulfikar, Achmad Jusuf; Siahaan, M Yusuf R; Irwan, Ade; Nasution, Fadly A. Kurniawan; Ritonga, Din Aswan A. (Rekayasa Material, Manufaktur dan Energi, 2022)
Shellfish is one of the sources of natural wealth that is quite abundant and easy to obtain in the province of Sumatera Utara. In this study, shellfish will be used as an alternative raw material for the manufacture of water pipes. This study aims to obtain the average strength of the material against the bending and compressive loads imposed on the outer surface of the water pipe, calculate the distribution of the test result data by the Probability Density Function (PDF) method, and calculate the contribution of clamshell powder to the bending and compressive strength of the water pipe with the Anova and Tukey methods. Specimens are molded in the form of 2" water pipes according to SNI standards 06-0084-2002. Bending and pressing testing using ASTM D7264 and ASTM D695 respectively. Processing the distribution of test data using the PDF method, the calculation of variable contributions using the Anova method, and the comparison between variables with the Tukey method. The result obtained the best bending strength at a composition of 10% by weight, namely 3.3177 MPa, and the best compressive strength at a composition of 50% by weight of 4.37 MPa. Based on the calculations of the Anova and Tukey methods, the application of clamshell powder significantly affects the bending strength compared to its compressive strength, which is the composition of 10% by weight.